Evaluando impactos externos mediante un Modelo de Equilibrio General Computable con Competencia Imperfecta: El caso Colombiano (2013)
Based on a computable general equilibrium model, in which an informal sector in the economy is discriminated, the formal sector is modeled as a monopolistic competition market. In addition to include discriminated labour markets, this model also includes the assessment impacts such as the increment of: foreign investment flows, price of commodities, and the volume of exports in the Colombian economy. This paper concludes that just over half of the observed growth can be explained by the effect of the above factors, and highlights the importance of domestic policies to take advantage of the good times, and to minimize the effect of negative circumstances on economic performance.